Nectários extraflorais em Luffa cylindrica (L.) M. Roem (Cucurbitaceae): anatomia e respostas morfofisiológicas em função do status nutricional e herbivoria - Poliana Fernandes Souza Lima (2016)
Extrafloral nectaries (EFNs) are secretory structures commonly involved in the indirect defence of plants. In Luffa cylindrica, these structures occur in leaves, stems and fruits. 3 In leaves, EFNs are present on the lower surface and the stipules, and can also occur 4 in the petiole and modified leaves such as bracts and bracteoles. EFNs are functional 5 and attract ants from the initial stages of the development of their associated organs 6 and the secretory activity is prolonged until the senescence of such organs. EFNs 7 differentiation and secretor process are generally induced by herbivory and/or artificial 8 damage and, consequently, are considered as a induced defence response. In this 9 work, the structural and ultrastructural organization of EFNs were studied; also, the 10 effects of different nutritional status and herbivory on the occurrence of nectaries 11 number and sugar concentration of nectar were analysed. Plants growing in three 12 different nutrient concentrations (10, 50 and 100% of nutrients in the nutritive solution) 13 were subjected to simulated herbivore, leaving a control group (i.e. without herbivory) 14 per nutrient concentration. Nectar was collected from all treatments to quantitative 15 analyses of sugars. Following the growth of ten leaves post-herbivory, leaf area was 16 measured and the nectary number was counted. There was significant variation in 17 nectary number per treatment, especially in plants growing at 10% with herbivory, 18 which showed less nectary density in relation to control plants. However, this pattern 19 was significantly related to leaf area increase in those plants suffering herbivory. The 20 results suggest that Luffa cylindrical allocates more resources in photosynthetic tissue 21 when subjected to herbivore attack under nutritional deficit. Likewise, plants growing 22 under suitable levels of nutrients invest in nectar containing a greater amount of 23 sugars.